Corticosteroid plus glycyrrhizin therapy for chronic drug‐ or herb‐induced liver injury achieves biochemical and histological improvements: a randomised open‐label trial. Issue 10 (31st March 2022) - Wang, Jia‐Bo; Huang, Ang; Wang, Yijin; Ji, Dong; Liang, Qing‐Sheng; Zhao, Jun; Zhou, Guangde; Liu, Shuhong; Niu, Ming; Sun, Ying; Tian, Hui; Teng, Guang‐Ju; et al.
Summary: Background: Treatment of chronic drug‐induced liver injury (DILI) or herb‐induced liver injury(HILI) is an important and unresolved challenge. There is no consensus regarding the indications for corticosteroids for chronic DILI/HILI. Aims: To investigate the efficacy and safety of corticosteroid plus glycyrrhizin for patients with chronic DILI/HILI. Methods: This was a randomised open‐label trial. Eligible patients with causality assessment using the updated RUCAM were randomly assigned (1:1) either to the steroid treatment group (48‐week stepwise dose reduction of methylprednisolone plus glycyrrhizin) or control group (glycyrrhizin alone). Liver biopsies were performed at baseline and at the end of the 48‐week treatment period. The primary outcome was the proportion of patients with sustained biochemical response (SBR). The secondary outcomes were improvement in liver histology, time to biochemical normalisation and safety. Results: Of 80 participants, 70 (87.5%) completed the trial. The patients were predominantly female (77.5%), aged >40 years (77.5%) and had a hepatocellular injury pattern of DILI (71.2%). Compared to the control group, the treatment group showed a higher proportion of SBR (94.3% vs. 71.4%, p  = 0.023), shorter biochemical normalisation time and histological improvements in both histological activity and fibrosis. The DILI and HILI subgroups, as well as the autoimmune hepatitis (AIH)‐like DILI and non‐AIH‐like subgroups, showed comparable responses. No severe adverse events were observed during the trial. Conclusion: This study provides the first clinical evidence that corticosteroid plus glycyrrhizin therapy for chronic DILI with or without AIH‐like features can achieve both biochemical response and histological improvements with good safety. (ClinicalTrials.gov, NCT 02651350).